Lexical Borrowings From The English Language Into Bangla Short Stories - Muhammad Azizul Hoque,; Md Maksud Ali,; Fariza Puteh-Behak,; Hazleena Baharun (Journal of Language and Linguistic Studies, 2024)
Indexed by Scopus